2019
DOI: 10.7554/elife.45205
|View full text |Cite
|
Sign up to set email alerts
|

Protein quality control in the nucleolus safeguards recovery of epigenetic regulators after heat shock

Abstract: Maintenance of epigenetic modifiers is of utmost importance to preserve the epigenome and consequently appropriate cellular functioning. Here, we analyzed Polycomb group protein (PcG) complex integrity in response to heat shock (HS). Upon HS, various Polycomb Repressive Complex (PRC)1 and PRC2 subunits, including CBX proteins, but also other chromatin regulators, are found to accumulate in the nucleolus. In parallel, binding of PRC1/2 to target genes is strongly reduced, coinciding with a dramatic loss of H2AK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 73 publications
4
51
1
Order By: Relevance
“…GO analysis of PIP2-effectors further identified proteins linked to proteasome, heat response, and nucleoli localization. Heat shock induced protein aggregates or misfolded proteins are directed to nucleoli [ 42 , 43 ]. The degradation of protein aggregates is in general mediated by proteasomal or autophagy processes [ 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GO analysis of PIP2-effectors further identified proteins linked to proteasome, heat response, and nucleoli localization. Heat shock induced protein aggregates or misfolded proteins are directed to nucleoli [ 42 , 43 ]. The degradation of protein aggregates is in general mediated by proteasomal or autophagy processes [ 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The degradation of protein aggregates is in general mediated by proteasomal or autophagy processes [ 44 , 45 , 46 ]. Ubiquitinated and heat shock proteins form aggresomes within the nucleolus [ 43 , 47 ] Proteins sensitive to heat shock denaturation, which are enriched for disordered regions, can be refolded within the nucleolus [ 42 ]. Nucleolar aggresomes contain proteins such as fibrillarin, ubiquitin, or autophagy factor LC3 [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, increasing studies have indicated that, in addition to the canonical functions of regulating ribosome biogenesis, the nucleolus also plays significant roles in protein quality control ( Frottin et al., 2019 ; Amer-Sarsour and Ashkenazi, 2019 ; Azkanaz et al., 2019 ; Rekulapally and Suresh, 2019 ) and degradation ( Song and Wu, 2005 ; Tao et al., 2013 ; Guan et al., 2016 ). For instance, Survivin-deltaEx3, a splice variant of Survivin, was reported to be degraded through the nucleolus-mediated protein degradation pathway in a ubiquitination-proteasome-dependent manner ( Song and Wu, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…This correlates with the predictive scoring of stress granule-associated proteins that suggests that various protein classes are capable of phase separation in different cellular locations [ 122 ]. Further work shows a reconfiguration of the localisation of QC machinery upon heat stress with chaperones accumulating in nucleoli [ 123 ]. These observations are intriguing as the proteostasis circuits that govern cytosolic and nuclear QC require distinct signals in the UPS [ 102 ].…”
Section: Compartmentalisation and Phase Separationmentioning
confidence: 99%